2015
DOI: 10.1007/s10589-015-9768-y
|View full text |Cite
|
Sign up to set email alerts
|

An acceleration scheme for Dykstra’s algorithm

Abstract: Dykstra's algorithm is an iterative alternating projection procedure for solving the best approximation problem: find the closest point, to a given one, in the intersection of a finite number of closed and convex sets. The main drawback of Dykstra's algorithm is its frequent slow convergence. In this work we develop an acceleration scheme with a strong geometrical flavor, which guarantees termination at the solution in two cycles of projections in the case of two closed subspaces. The proposed scheme can also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…As a final experiment we use the four matrices from Experiment 1 to compare Anderson acceleration with the acceleration scheme from [29]. Table 10 shows the number of iterations, it 2, for that scheme, in which we set its safeguard parameter ε to 10 −14 and use the same convergence tolerance as in all our experiments.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…As a final experiment we use the four matrices from Experiment 1 to compare Anderson acceleration with the acceleration scheme from [29]. Table 10 shows the number of iterations, it 2, for that scheme, in which we set its safeguard parameter ε to 10 −14 and use the same convergence tolerance as in all our experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The number of iterations for the acceleration scheme is the same as for the unaccelerated method in each case except for the matrix with n = 6, and in that case we see a reduction in the number of iterations by a factor 1.1 versus 3.8 for Anderson acceleration. In all test cases, after a few initial iterations the mixing parameter α k needed for the scheme [29] could not be computed because the safeguard was triggered. We conclude that the acceleration scheme of [29] is not To summarize, in these experiments we have found that Anderson acceleration of the alternating projections method for the nearest correlation matrix, with an appropriate choice of m ∈ [1,6], results in a reduction in the number of iterations by a factor of at least 2 for the standard algorithm and a factor at least 3 when additional constraints are included.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations